2009
DOI: 10.1182/blood.v114.22.2153.2153
|View full text |Cite
|
Sign up to set email alerts
|

Poor Mobilization of Hematopoietic Stem Cells – Definitions, Incidence, Risk Factors and Impact On Outcome of Autologous Transplantation.

Abstract: 2153 Poster Board II-130 Hematopoietic progenitor and stem cells (HSC) reside in the bone marrow and have to be mobilized into the circulation prior to being collected by apheresis. The number of apheresis procedures needed and the success of transplantation are determined by the efficiency of stem cell mobilization. Between January 2004 to December 2008, 840 patients (pt) with the following diagnoses were scheduled to undergo leukapheresis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
138
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(147 citation statements)
references
References 0 publications
7
138
0
2
Order By: Relevance
“…Furthermore, in our program, we recommend non-lenalidomide containing induction therapy, mainly cyclophosphamide/bortezomib/dexamethasone, which may explain the lower number of patients who received lenalidomide in their first induction regimen and possibly the relatively lower frequency of poor mobilizers (10.4%), whereas many other studies reported > 15% incidence. 21,22 Another possible limitation is the relatively small number of patients treated with CXCR4 antagonist plerixafor. Due to its effectiveness in reducing the number of poor mobilizers, many institutions now routinely utilize plerixafor for PBSC mobilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our program, we recommend non-lenalidomide containing induction therapy, mainly cyclophosphamide/bortezomib/dexamethasone, which may explain the lower number of patients who received lenalidomide in their first induction regimen and possibly the relatively lower frequency of poor mobilizers (10.4%), whereas many other studies reported > 15% incidence. 21,22 Another possible limitation is the relatively small number of patients treated with CXCR4 antagonist plerixafor. Due to its effectiveness in reducing the number of poor mobilizers, many institutions now routinely utilize plerixafor for PBSC mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Most studies use different definitions for poor mobilization in MM patients, mainly due to the practice of collecting upfront adequate numbers of stem cells for two transplants. [20][21][22] Poor mobilization prior to ASCT has important prognostic implications. In lymphoma, work from our institution demonstrated poor mobilizers (defined as inability to obtain 1 3 10 6 CD341 cells/kg ideal body weight [IBW] with two large volume apheresis) had a shortened PFS and OS compared to patients who were good mobilizers.…”
Section: Introductionmentioning
confidence: 99%
“…It is also applied in the treatment of various types of neutropenia (Gabrilove et al, 1988;Hoggatt & Pelus, 2014). Although G-CSF was successfully introduced to clinical practice, there are cases when G-CSF treatment remains inefficient (Wuchter et al, 2010;To et al, 2011). One of the proposed strategies to overcome these limitations would imply induction of endogenous G-CSF expression by drug administration rather than administration of recombinant G-CSF itself (Hoggatt & Pelus, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…9 The authors reported on a daily complete blood count the obtained results should be interpreted with cautiousness, as a substantial variation of mobilized stem cells can be observed and poor and mega-mobilizers can be found even in a homogeneous patient population. 26 Future studies should also analyze the role of immunocompetent cell subsets in the stem cell graft.…”
Section: Discussionmentioning
confidence: 99%